Zadovoljstvo bolnikov na Oddelku intenzivne nege in terapije Bolnišnice Golnik - Prestor, Alojzija (Obzornik zdravstvene nege, 2002)
The article deals with the satisfaction of patients on the Intensive Therapy and Care Ward of the Hospital for Lung and Allergic Diseases Golnik. Data weregathered by means of a questionnaire containing questions on information to patients about their rights upon admission, on attitude of the staff towards patients, on information delivered to them about their health, on therapy and nursing care, on visits and some general questions. In the end, wealso enquired about patients' relatives satisfaction. 198 patients were included in the research study.
Keywords: ankete; Bolnik, zadovoljstvo; bolniki; Enote za intenzivno medicino; health care; Intensive care units; intenzivna terapija; Lung diseases; Medicinska sestra-bolnik, odnosi; Nurse-patient relations; Nursing; Patient satisfaction; Pljuča, bolezni; pljučne bolezni; Questionnaires; therapy; zdravljenje; zdravstvo